2007
DOI: 10.1099/mic.0.2006/001636-0
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-β-cyclodextrin alters growth, activity and cell envelope features of sterol-transforming mycobacteria

Abstract: Modified b-cyclodextrins have been shown previously to enhance sterol conversion to 4-androstene-3,17-dione (AD) and 1,4-androstadiene-3,17-dione (ADD) by growing Mycobacterium spp. The enhancement effect was mainly attributed to steroid solubilization by the formation of inclusion complexes with modified cyclodextrins. In this work, the influence of randomly methylated b-cyclodextrin (MCD) on the growth, AD-and ADD-producing activity, cell wall (CW) composition and ultrastructure of sterol-transforming Mycoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 39 publications
(56 reference statements)
6
34
0
Order By: Relevance
“…In addition, the observed by SEM and TEM exfoliation of the electron dense capsule-like material and its partial disappearance from the Tween 80-grown possibly further contributes to lowering the cell surface hydrophobicity. Similar loss of hydrophobicity with parallel loss of surface lipids and mycolic acids were reported for the closely related mycobacteria and corynebacteria (Donova et al 2007;Puech et al 2001).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, the observed by SEM and TEM exfoliation of the electron dense capsule-like material and its partial disappearance from the Tween 80-grown possibly further contributes to lowering the cell surface hydrophobicity. Similar loss of hydrophobicity with parallel loss of surface lipids and mycolic acids were reported for the closely related mycobacteria and corynebacteria (Donova et al 2007;Puech et al 2001).…”
Section: Discussionsupporting
confidence: 77%
“…Aqueous-organic solvent two-phase systems where the water-immiscible organic solvent contained the steroid substrate are also applied (Angelova et al 2005). Only a few reports, however, associate the effect of the compounds applied to enhance the steroid substrates solubilization (such as lecitin, cyclodextrin and bis(2-ethylhexyl)phthalate) with their impact on the cell viability and morphology, microbial cell wall and cellular membranes (de Carvalho et al 2004a, b;Donova et al 2007;Rumijowska et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, CDs may facilitate the transport of poorly soluble hydrophobic substances to and from microbial cells, thus functioning as effective substrate/product delivery systems. As reported, CDs themselves do not penetrate through bacterial cell membranes, but can disrupt the outermost cell wall layers of the gram-positive bacteria [36]. The detail study of MCD effect on the cells of E. coli is out of the purposes of the current work, and can be investigated especially.…”
Section: Activity Of Bovine Ch/l System Reconstructed In Bacterial Cellsmentioning
confidence: 85%
“…It indicated that there was a slight improvement of the A. simplex TCCC 11037 cell's catalytic activity after being incubated in HP-β-CD solution. This could be ascribed to the interaction between CDs and cell membrane or cell wall by virtue of either their complexing ability and/or surface activity as mentioned by Donova and Nikolayeva [21]. Thus, HP-β-CD would be an excellent additive to retain the enzyme stability than DMF or ethanol in phosphate buffer.…”
Section: Effect Of Additives On Enzymatic Stabilitymentioning
confidence: 97%